2017
DOI: 10.1017/s0007114517002781
|View full text |Cite
|
Sign up to set email alerts
|

Effect of fibre additions to flatbread flour mixes on glucose kinetics: a randomised controlled trial

Abstract: We previously found that guar gum (GG) and chickpea flour (CPF) added to flatbread wheat flour lowered postprandial blood glucose (PPG) and insulin responses dose dependently. However, rates of glucose influx cannot be determined from PPG, which integrates rates of influx, tissue disposal and hepatic glucose production. The objective was to quantify rates of glucose influx and related fluxes as contributors to changes in PPG with GG and CPF additions to wheat-based flatbreads. In a randomised cross-over design… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 64 publications
0
20
0
Order By: Relevance
“…To evaluate whether the modified formulation impacts the plasma metabolome, we started to determine the postprandial levels of plasma metabolite. Data on insulin and incretin responses were published by Boers et al [19] and are provided in Suppl. Table S1.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To evaluate whether the modified formulation impacts the plasma metabolome, we started to determine the postprandial levels of plasma metabolite. Data on insulin and incretin responses were published by Boers et al [19] and are provided in Suppl. Table S1.…”
Section: Resultsmentioning
confidence: 99%
“…But testing for this hypothesis requires information on the dynamics of glucose metabolism considering that the postprandial glucose response is the integrated result of the rate of appearance of exogenous glucose, rate of disappearance of total glucose and the endogenous glucose production in the liver [18]. Using the dual tracer approach, Boers et al showed that guar gum supplementation reduced the rates of exogenous glucose appearance, but also had substantial effects on the rates of postprandial disposal and endogenous glucose production [19]. This suggests that the addition of the fiber mix not only affects gastric emptying and the digestion process in the intestine, as expected [16], but also impacts other metabolic rates.…”
Section: Introductionmentioning
confidence: 99%
“…Resistant starch reportedly plays a role in controlling blood glucose and insulin levels [39,40]. Additionally, potato flour contains a large amount of fiber, which is beneficial to slowing down the postprandial glucose increase [41].…”
Section: Discussionmentioning
confidence: 99%
“…This is important because it has been suggested that reductions in glycaemic response are only beneficial if they are accompanied by reductions in insulin response of a similar (or greater) magnitude [28, 29]. Reduced postprandial glucose responses can be due either to a reduced rate of entry of glucose into the circulation [30] or to reduced hepatic glucose production [31] or to an increased rate of glucose disposal because of an increased insulin response. Since we found no evidence of disproportionately high insulin responses, the present results support the hypothesis that ONO and ONOsns reduced glycaemic responses because they contain slowly absorbed carbohydrates.…”
Section: Discussionmentioning
confidence: 99%